THE SENIOR COMPANION PROGRAM PLUS: A PEER-LED MODEL FOR CULTURALLY-INFORMED FAMILY CAREGIVER INTERVENTIONS. (11th November 2018) - Fields, N; Xu, L; Parekh, R
Abstract: Research related to African American (AA) Alzheimer's disease and related dementia (ADRD) family caregivers have been mixed with regard to caregiver burden, stress, depression, and anxiety. Almost all previous interventions are based on conceptual models and intervention protocols that have used professionals instead of lay persons or peers who are "insiders" and who know the culture and needs of the AA community. This study used a peer-led model to inform the design of an intervention using the Senior Companion Program. Though three focus groups (N = 18), AA Senior Companions shared their cultural beliefs, values, and needs, in the design and development of the Senior Companion Program Plus (SCP Plus), an intervention for AA ADRD family caregivers. We transcribed the focus groups and used directed content analysis to analyze the data. Participants identified that combatting the myths of ADRD and overcoming the stigma associated with ADRD in the AA community was particularly important to include in the SCP Plus. Communicating with health care professionals was also identified as a concern for AA ADRD caregivers given the realities of discrimination and racism that many individuals face in the community. Finally, the Senior Companions recommended highlighting religion and/or spirituality as a positive coping resource for AA ADRD caregivers as a key component of the SCP Plus. Study findings have implications for the use of peer-led providers to inform culturally-tailored interventions, and we offer recommendations for the use of the Senior Companion Program as a platform for ADRD family caregiver interventions.